Prevalence of Seed Borne Fungi Associated with Chickpea Seeds and Biological and Chemical Control of Fusarium oxysporum Causing Wilt Disease - Hossain, MD; Imran, M; Bhuiyan, KA; Habib, ME; Ikrum, M (Journal of Environmental Science and Natural Resources, 2018)
A total of 20 chickpea seed samples were collected from BARI, Gazipurand different locations of Savar, Dhaka district. Blotter method was used for detection of the associated fungi of chickpea seeds. Altogether 14 fungi comprising 12 genera namely Aspergillus flavus, Aspergillus niger, Aspergillus sp, Botryodiplodia theobromae, Botryti cinerea, Curvularia lunata, Chaetomium globosum, Cladosporium sp., Colletotrichum dematium, Fusarium oxysporum, Macrophomina phasaelina, Rhizoctonia solani, Rhizopus stolonifer and Stemphylium sarciniforme were isolated from chickpea seed samples. Among the fungi isolated fungi, F. oxysporumwas most prevalent with an average incidence of 18.95% and found in all the seed samples. The germination of seed samples varied from 55-90 % on blotter. The pathogenic fungi and other storage fungi like Aspergillus caused lower the germination of the seeds.A pathogenicity test was conducted with 20 isolates of F. oxysporum against their origin of chickpea seed samples in pot culture. The pathogenecity ranged from weak to highly pathogenic. The isolates FO 19, FO 17, FO 11 and FO 18 were highly virulent. The isolates FO 9, FO10 and FO 15 were virulent and rest of the isolates were moderately virulent. The isolates FO 2 and FO 3 were weak pathogen. J. Environ. Sci. & Natural Resources, 10(2): 45-54 2017